2020
DOI: 10.1186/s13075-020-02345-2
|View full text |Cite
|
Sign up to set email alerts
|

Pain sensitivity in young adults with juvenile idiopathic arthritis: a quantitative sensory testing study

Abstract: Background To study for the first-time, pain perception, pain sensitivity, and self-reported pain in young adults with long disease duration of juvenile idiopathic arthritis (JIA) compared with controls. Methods Children from Central Norway diagnosed with JIA between 1997 and 2004 were included consecutively in a population-based prospective study. Children with onset 1997–2000 were part of the Nordic JIA cohort. Controls were age- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…It is worth mentioning that apart from HPT, in this cross-sectional study, no QST modalities had a significant correlation with the magnitude of the reported pain. This is in accordance with the findings of Arnstad et al [ 17 ] It is well known that the perception of pain is the result of complex biopsychosocial processing. Whether or not such a correlation between QST and reported magnitude of pain exists should be investigated in future longitudinal studies, or larger cross-sectional studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is worth mentioning that apart from HPT, in this cross-sectional study, no QST modalities had a significant correlation with the magnitude of the reported pain. This is in accordance with the findings of Arnstad et al [ 17 ] It is well known that the perception of pain is the result of complex biopsychosocial processing. Whether or not such a correlation between QST and reported magnitude of pain exists should be investigated in future longitudinal studies, or larger cross-sectional studies.…”
Section: Discussionsupporting
confidence: 93%
“…A validated QST protocol was originally developed for testing the somatosensory system in adults [ 12 15 ], and the QST protocol was validated in healthy children from 5 years and older [ 13 ]. A few studies using QST in children with JIA showed an increased sensitivity to painful mechanical and thermal stimuli at the thenar eminence and knee; even in absence of markers of disease activity, and for a prolonged period of time [ 16 , 17 ]. However, each joint is differently innervated and sensitivity levels differ depending on the tested location (e.g., the face yields different values from the hand) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…and the QST protocol was validated in healthy children from 5 years and older [11]. A few studies using QST in children with JIA showed an increased sensitivity to painful mechanical and thermal stimuli at the thenar eminence and knee; even in absence of markers of disease activity, and for a prolonged period of time [14,15]. However, each joint is differently innervated and sensitivity levels differ depending on the tested location (e.g., the face yields different values from the hand) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite juvenile idiopathic arthritis (JIA) being the most common, chronic rheumatic condition of childhood, children frequently have symptoms for months to years before presenting to a pediatric rheumatologist and receiving a diagnosis ( 1 , 2 , 3 ). Untreated juvenile arthritis can lead to chronic pain, muscle atrophy, joint contractures, limb‐length discrepancies, and abnormal growth ( 4 , 5 , 6 , 7 ). It is suggested that there is a critical window of opportunity to diagnose and treat this disease, and early treatment may limit unfavorable outcomes ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%